2021
DOI: 10.1128/msphere.00934-20
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Host Cytosolic Protein by Toxoplasma gondii Bradyzoites

Abstract: Toxoplasma gondii is a protozoan parasite that persists in the central nervous system as intracellular chronic-stage bradyzoites that are encapsulated by a thick cyst wall. While the cyst wall separates bradyzoites from the host cytosol, it has been posited that small solutes can traverse the cyst wall to sustain bradyzoites. Recently, it was found that host cytosolic macromolecules can cross the parasitophorous vacuole and are ingested and digested by actively replicating acute-stage tachyzoites. However, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…We propose two possibilities, that bradyzoites uptake host proteins that are trafficked to the VAC for degradation via the endolysosomal system or that, in the absence of TgATG9, bradyzoites have an alternative mechanism of autophagy. The first hypothesis is supported by our recent work, which demonstrated that bradyzoites can ingest and degrade host-derived cytosolic proteins ( Kannan et al, 2021 ). In the second possibility, as discussed further below, we observed the formation of vesicles with two or more membranes in ∆atg9 bradyzoites by TEM and while we are currently unable to determine the nature of these vesicles, it remains possible that they represent alternative autophagosome-like structures that do not stain well with the cationic amphiphilic dye CytoID.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We propose two possibilities, that bradyzoites uptake host proteins that are trafficked to the VAC for degradation via the endolysosomal system or that, in the absence of TgATG9, bradyzoites have an alternative mechanism of autophagy. The first hypothesis is supported by our recent work, which demonstrated that bradyzoites can ingest and degrade host-derived cytosolic proteins ( Kannan et al, 2021 ). In the second possibility, as discussed further below, we observed the formation of vesicles with two or more membranes in ∆atg9 bradyzoites by TEM and while we are currently unable to determine the nature of these vesicles, it remains possible that they represent alternative autophagosome-like structures that do not stain well with the cationic amphiphilic dye CytoID.…”
Section: Discussionmentioning
confidence: 83%
“…However, this also raises the question as to how T. gondii tissue cysts containing bradyzoites are able to persist within the host with potentially limited access to host material for sustenance. Although recent work reported that T. gondii bradyzoites can ingest and digest protein from the cytosol of infected cells in vitro ( Kannan et al, 2021 ), the extent to which this process helps to sustain bradyzoites remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…GRA2 and GRA6, through lipid binding (55), form membrane tubules that are involved in heterophagic ingestion of host cell proteins (56), Rab-positive host cell vesicles (57), and Rab7-positive host lipid droplets (20). Acquisition of host cell cargo and digestion are also likely to be essential for chronic infection (58), and recently published evidence supports the hypothesis that encysted bradyzoites have the capability to import host cell proteins and cargo (59).…”
Section: Discussionmentioning
confidence: 94%
“…While long considered to be inert, it is now recognized that bradyzoites undergo episodic bursts of proliferation, internalize host-derived macromolecules, and export parasite effectors (Kannan et al, 2021;Watts et al, 2015). The cyst wall is an important interface between host and parasite that sits just below the PVM (Guevara et al, 2020;Tu et al, 2020;Young et al, 2020), and not every protein that can escape from the PVM in tachyzoites can cross the cyst wall (Krishnamurthy and Saeij, 2018).…”
Section: Latency and Subversionmentioning
confidence: 99%